ANALISIS PESAN DAN DAMPAK ANIME BERGENRE AKSI PADA MAHASISWA UNIVERSITAS ISLAM NEGERI AR-RANIRY BANDA ACEH - Hanifah Nurdin; Ade Irma; Azman Sulaiman; Miftahul Jannah; Al Zuhri (Program Studi Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas Sumatera Selatan, 2023)
Anime shows are popular among the students of Uiniversitas Islam Negeri Ar-Raniry Banda Aceh. The students love to watch action anime. Action anime is one of the anime that has many fans. Featuring diverse stories that want to eradicate the evils of the world. As a result of watching the anime, UIN Ar-Raniry students have a habit of speaking harshly using Japanese, limiting associations, lacking socialism, lacking nationalism, hallucinating people, and considering to adapt Japanese culture. This study aims to find the message and impact of anime communication in the action genre. The research method used is qualitative with an analytical descriptive approach. As for the results found, there are positive and negative messages on the spectacle of action genre anime that have an effect on UIN Ar-Raniry students such as responsibility, wisdom, sacrifice, cooperation, daring to dream, grateful, never giving up, respecting each other, solidarity, science, technology, pioneering, caste differences, genocides, and corruption. The anima shows give impact to the viewers. There are positive and negative impacts in watching action genre anime that can have an effect on student life after visiting.